2009
DOI: 10.1074/jbc.m807478200
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a Third EspA-binding Protein That Forms Part of the Type III Secretion System of Enterohemorrhagic Escherichia coli

Abstract: Enterohemorrhagic Escherichia coli utilizes a type III secretion system to deliver virulent effectors into cells. The secretion apparatus comprises a membrane basal body and an external needle complex of which EspA is the major component. An l0050-deletion (⌬L50) mutation was found to impair type III secretion and bacterial adherence. These phenotypes and the localization of the gene product to the inner membrane support the hypothesis that L0050, renamed EscL, forms part of the secretion apparatus. Furthermor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
16
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 40 publications
(49 reference statements)
2
16
0
Order By: Relevance
“…The null strains showed defective secretion, indicating that EscL, EscN, and EscQ are essential for T3S (Fig. 1A), in agreement with the observations previously reported for Citrobacter rodentium and EHEC (3,16). Complementation of the null strains with double-hemagglutinin (HA)-tagged EscL, EscN, or EscQ in trans (cloned into pTOPO-2HA [3] by the use of HindIII and XhoI sites with the primer pairs shown in Table 1) restored secretion of the translocators, thus confirming that the deletion mutations in escL, escN, and escQ were nonpolar and that the tagged versions of these proteins were functional (Fig.…”
supporting
confidence: 81%
“…The null strains showed defective secretion, indicating that EscL, EscN, and EscQ are essential for T3S (Fig. 1A), in agreement with the observations previously reported for Citrobacter rodentium and EHEC (3,16). Complementation of the null strains with double-hemagglutinin (HA)-tagged EscL, EscN, or EscQ in trans (cloned into pTOPO-2HA [3] by the use of HindIII and XhoI sites with the primer pairs shown in Table 1) restored secretion of the translocators, thus confirming that the deletion mutations in escL, escN, and escQ were nonpolar and that the tagged versions of these proteins were functional (Fig.…”
supporting
confidence: 81%
“…Alternatively, EscK and EscL may directly participate as docking sites for T3S substrates. Indeed, EscL has been shown to bind EspA (82). Moreover, it is interesting that proteins of the SctK family are the less-conserved constituents of the sorting platform structure.…”
Section: Discussionmentioning
confidence: 99%
“…These chaperones increase the stability of EspA and show direct EspA-binding activity (12,13,52). Recently, it has been reported that EscL, in addition to CesAB and CesA2, interacts directly with EspA, enhances the stability of intracellular EspA, and is also essential for the complete secretion of EspA (33). Similarly, we found that two small T3SS molecules, SsaE and SseA, function as chaperones for the Salmonella SPI-2 translocator SseB, an EspA homologue.…”
Section: Discussionmentioning
confidence: 53%